2018
DOI: 10.20944/preprints201809.0244.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Single Tube Contactor for Testing Membrane Ozonation

Abstract: A membrane ozonation contactor was built to investigate ozonation using tubular membranes and to inform computational fluid dynamics (CFD) studies. Non-porous tubular polydimethylsiloxane (PDMS) membranes of 1.0 – 3.2 mm inner diameter were tested at ozone gas concentrations of 110 – 200 g m−3 and liquid side velocities of 0.002 m s−1 – 0.226 m s−1. The dissolved ozone concentration could be adjusted to up to 14 mg O3 L−1 and increased with decreasing membrane diameter and liquid side velocity. Experimental ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…29 In general, the higher the liquid velocity, the higher the expected diffusion rate, 31 up to a maximal diffusion capacity of the membrane. 21,32 Previous studies examined ozone diffusion rates in extremely high liquid velocities (up to three orders of magnitude higher than the velocities applied in the current study), though the obtained ozone diffusion rate values were comparable to those reported here. 21,32 For example, experimental diffusion rate values of 2 to 10 μmol s −1 m −2 were reported by Zoumpouli et al for a PDMS membrane with 0.6 mm wall thickness, 110− 200 g m −3 ozone gas concentration, and up to 0.25 m s −1 liquid velocity.…”
Section: Effect Of Liquid Velocity On Dissolved Ozone Concentrations ...supporting
confidence: 84%
See 2 more Smart Citations
“…29 In general, the higher the liquid velocity, the higher the expected diffusion rate, 31 up to a maximal diffusion capacity of the membrane. 21,32 Previous studies examined ozone diffusion rates in extremely high liquid velocities (up to three orders of magnitude higher than the velocities applied in the current study), though the obtained ozone diffusion rate values were comparable to those reported here. 21,32 For example, experimental diffusion rate values of 2 to 10 μmol s −1 m −2 were reported by Zoumpouli et al for a PDMS membrane with 0.6 mm wall thickness, 110− 200 g m −3 ozone gas concentration, and up to 0.25 m s −1 liquid velocity.…”
Section: Effect Of Liquid Velocity On Dissolved Ozone Concentrations ...supporting
confidence: 84%
“…21,32 Previous studies examined ozone diffusion rates in extremely high liquid velocities (up to three orders of magnitude higher than the velocities applied in the current study), though the obtained ozone diffusion rate values were comparable to those reported here. 21,32 For example, experimental diffusion rate values of 2 to 10 μmol s −1 m −2 were reported by Zoumpouli et al for a PDMS membrane with 0.6 mm wall thickness, 110− 200 g m −3 ozone gas concentration, and up to 0.25 m s −1 liquid velocity. 32 In another study, where a porous membrane was used as a gas contactor, the obtained ozone diffusion rates were 2−3 μmol s −1 m −2 .…”
Section: Effect Of Liquid Velocity On Dissolved Ozone Concentrations ...supporting
confidence: 84%
See 1 more Smart Citation
“…This continuous operation enables the combination of multiple treatment processes. A lab-scale ozonation combined with a post-treatment biological active sand ltration in a continuous experimental setup has already been established [101]. Due to the modular nature of the experimental setup, it is possible to investigate different water treatment schemes through rearranging the treatment modules.…”
Section: Methodsmentioning
confidence: 99%